Meningkatkan Literasi Digital Siswa di Sekolah Dasar - Adien Inayah; Aflah Husnaini Matondang; Diana Pauziah Ritonga; Friska Widia; Novita Sari Nasution (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
Digital literacy is very important in education today, especially at the elementary school level. This article aims to explore strategies and challenges in increasing students' digital literacy in elementary schools in the digital era. The research method used is a literature study to analyze factors increasing digital literacy, such as curriculum development, teacher training, infrastructure access and technological resources. This research focuses on the importance of increasing students' digital literacy in elementary schools in the digital era, with a focus on challenges, strategies and factors for increasing digital literacy. The research results show that adequate access to technology infrastructure and resources, as well as parental involvement, are critical in increasing digital literacy. Challenges such as social and economic disparities, technology management, and resistance to change must be overcome with character strengthening strategies, understanding the importance of digital literacy, and collaboration from all stakeholders. A comprehensive and coordinated approach is needed to achieve optimal results in improving students' digital literacy in elementary schools.